Energy change and space motion of electron in sinusoidal field with random phase jumps or elastic collisions - Ostroushko, V. (Вопросы атомной науки и техники, 2015)
Two different types of electron motion are considered: the one-dimensional motion in the electric field, which time dependence differs from sinusoidal one through instant jumps of phase, and the three-dimensional motion in the sinusoidal field interrupted with elastic collisions. The dependencies of the characteristic electron energy and of the characteristic dimensions of the space required for electron motion on the number of phase jumps or elastic collisions are obtained.